Global burden of tracheal, bronchus, and lung cancer attributable to second-hand smoke exposure from 1992 to 2021: an age-period-cohort analysis and 25-year mortality projections - Lin, Hong-ming; Lin, Bin; Liao, Xin-peng; Hong, Hong; Cai, Xue-ting; Zhuang, Xi-bin (Frontiers in Public Health, 2025)
BackgroundTracheal, bronchus, and lung (TBL) cancer remains the leading cause of cancer-related mortality worldwide. While smoking is the primary risk factor, several non-smoking-related factors also significantly contribute to TBL cancer, notably second-hand smoke (SHS) exposure, which plays a substantial role in the disease’s burden. This study assesses and forecasts the temporal trends in the disease burden of TBL cancer attributable to SHS exposure at global, regional, and national levels.MethodsWe extracted data from the ≥ 25 years population in the Global Burden of Disease Study 2021 (GBD 2021) to assess deaths, disability-adjusted life years (DALYs), age-standardized mortality rate (ASMR), and age-standardized DALY rate (ASDR) at both global and regional levels. We evaluated temporal trends using descriptive statistics, estimated annual percentage change (EAPC), and both the age-period-cohort (APC) and Bayesian age-period-cohort (BAPC) models.ResultsFrom 1992 to 2021, absolute deaths and DALYs linked to TBL cancer due to SHS exposure increased, although ASMR and ASDR showed declining trends, with EAPC values of −0.92% and −1.30%, respectively. Regions with a high socio-demographic index (SDI) displayed the most significant improvements. In contrast, high-middle and middle SDI regions bore the greatest disease burden, and low SDI regions saw minimal progress. The highest ASMR in 2021 occurred mainly in Western Europe, North America, and East Asia, with ASMR correlating positively with SDI. The disease burden was consistently higher among males, particularly in the 65–74 age group, across both sexes. Future projections indicate a continuing decline in the disease burden from 2022 to 2046.ConclusionSHS exposure continues to be a significant factor in the disease burden of TBL cancer. Although there has been an overall declining trend globally, it still caused the deaths of more than 97,000 people in 2021. There exists considerable heterogeneity among regions, with some areas still bearing a substantial disease burden. These findings highlight the need for specific prevention and control strategies to mitigate the health impacts of SHS exposure.